PENGARUH PENDIDIKAN KESEHATAN MEDIA AUDIO VISUAL TENTANG STUNTING TERHADAP PENGETAHUAN DAN SIKAP IBU BALITA DI DESA MUARA ADANG - El Has, Imaduddin Maulana; Hazanah, Sri; Bernadetha (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Stunting is a condition that signifies characterized by insufficient child growth, impacting both their physical and cognitive development. This condition stems from prolonged malnutrition, resulting in children being shorter than their peers and experiencing cognitive delays. The aim of this research was to explore how educating mothers of toddlers in Muara Adang Village about stunting through audio-visual media could affect their knowledge and attitudes toward this issue. This research utilized a quantitative research design, employing a Quasi-Experimental approach., specifically employing a one-group pretest-posttest methodology. The study population consisted of 56 individuals selected through purposive sampling. Data collection involved the use of pretest and posttest questionnaires and employed the The Wilcoxon test was performed with a significance level of p = 0.05. The results demonstrated a significant effect of health education delivered through audiovisual media on the knowledge of mothers in Muara Adang Village, as indicated by The p-value obtained was 0.000 (<0.05). Additionally, there was a significant impact of health education through audiovisual media on the dental and oral hygiene practices of mothers in Muara Adang Village, as indicated by a p-value of 0.002 (<0.05). Consequently, the delivery of health education through audiovisual media effectively improved mothers' understanding of stunting, their practices related to oral hygiene, and their overall expectations. This educational approach empowered them to enhance their knowledge of stunting by actively seeking information independently from various sources.